La protección del ambiente - Ramón Cují, María Fernanda (2017)
The present research does the problematic about "The environment Protection"; which allows us to verify at present how it finds the natural resources through research methods to make aware to all people who live in world. Because part of the solution is to achieve a greater degree of responsibility in the students, and something that it does generate a great impact that sooner or later will be returned to us and will be impossible development any kind of life including human one. The “Federico González Suarez” Educational Unit from Salcedo canton with the performance research it could make aware in the environment and the community, set up students in order to take care and protect the environment, beside they learn to classify the garbage and carry the message to their families creating healthy environments. The objective of the research is to improve the practice of the habits of hygiene, care and protection of the environment through recycling to avoid environmental pollution. And the specific objectives is to promote in students the change of attitudes through educational talks....